Experimental investigation and parametric optimization during EDM of Titanium grade 9 using MOORA-fuzzy integrated multi-objective Genetic algorithm. (2022) - Kumar, Anshuman; Vivekananda, Kukkala; Ram Prasad, A.V.S.
Abstract: The current work investigates an experimental study and potential of multi-objective optimization of machining performance characteristics "Material Removal Rate" (MRR) and "Tool Wear Rate" (TWR) during the "Electro-Discharge Machining" (EDM) process of Titanium grade 9 (Ti-3Al-2.5 V) (Ti G9). The Taguchi's L9 OA has been employed for selecting the appropriate outline of the experiment by varying Spark-on time (Son ), Spark-off time (Soff ), Peak Current (Ip ), and Gap Voltage (Vg ). A hybrid technique called MOORA-Fuzzy Integrated multi-optimization GA has been proposed to determine the best satisfactory machining performances. The most favorable machining parameter obtained through optimization technique as [Son  = 100 µs, Soff  = 100 µs, Ip  = 7A, and Vg  = 70 V] for maximize MRR and minimize TWR. In the present study, the proposed optimization technique can be capable enough to solve the multi-process optimization problems of the EDM process. Moreover, it is apparent very helpful in the manufacturing sectors, reducing machining time and improving productivity.